(untitled) (Academia Journal of Medicine, 2020)
Background: Hyponatremia develops in early phases of acute myocardial infarction, recently, several studies showing its importance as important early prognostic tool. Many studies shown that significant increase in plasma AVP level was in patients who had associated with complication as heart failure and fatal outcome after acute MI, and clinical improvement was noted following the rise in serum plasma level of sodium. hence Early developed hyponatremia is a unique indicator of neuro hormonal activity in the early phases of recent MI, so it can help predict the complication as long-term development of HF and death. OBJECTIVE: To observe the prognostic importance of hyponatremia in settings of acute STEMI event and helpfulness in prediction of short term and long term survival. Subjects and Methods: Randomized double blinded study, in 100 of patients with acute S TEMI presented to outpatient department and indoor emergency patients. Results: Patients who developed hyponatremia at admission had higher mortality rate than the patients who developed hyponatremia at 72 hrs and normonatremic patients. Mortality in patients correlates with the severity of hyponatremia 5(100%) patient died with sodium levels <130mmol/l whereas 5(16%) death occurred in the patient having sodium level between 131-134. (Odds ratio 6.0, p value 0.02). Conclusion: We concluded that hyponatremia developed in early as well as late phases of acute STEMI serve as is an ‘independent determinant of both short term (in hospital mortality, development of arrhythmias and heart failure) as well as long term survival (cardiac death, post discharge heart failure). Plasma sodium levels may help identify patient at risk.